S. MENDESHEV IS A PERSON WHO REPRESENTED THE INTERESTS OF KYRGYZSTAN IN THE PARITY COMMISSION OF 1927. (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article, along with a biography of Seitkali Mendeshev, a prominent figure of the Kazakh people and a member of the parity commission established by the decree of the Secretariat of the Central Executive Committee of the USSR on December 21, 1926, analyzed his work in the parity commission as a representative defending the interests of the Kyrgyz ASSR, based on relevant archival materials. Taking into account the criticism expressed in S. Mendeshev’s report of February 14, 1927, the Presidium of the All-Russian Central Executive Committee fully supported the decisions of the parity commission.
Keywords: border, municipality, parity commission, Central Asia, autonomy.